Os caminhos da persuasão sob a perspectiva da metafunção interpessoal em uma entrevista de talk show - Rigante, Tatiana (2008)
The amount of research about interviews in talk-shows and the way this gender is approached is scarce in Brazil. In this perspective, the present study aims at analyzing the persuasion which permeates the conversation turns in an interview with the deputy Denise Frossard, on Jô talk show program, with a view to answering the following question: what discursive resources Jô Soares and Denise Frossard mostly employ to persuade their audience in the interview? Considering the dynamics of the realizations of various meaning combinations which this analysis implies, my study has an eclectic theoretical support, including Fowler (1991), based on Critical Discourse Analysis, and theories complementing the Systemic-Functional Linguistics, particularly the interpersonal metafunction. In so being, I make use of these persuasive notions which help me understand both explicit and implicit persuasion that pervade the interview interloctions, according to the following elements: dialogism (Bakhtin, 1981); frame and footing (Goffman, 1981), smuggling information (Luchjenbroers e Aldridge, 2007); directed information (Coffin e O Halloran, 2006), notions of cryptic-argumentation (Kitis e Milapides, 1996) and finally Analysis of Conversation (Eggins e Slade, 1997), which sheds light on the existing phenomena in the conversation turns. The data showed that amongst the occurrent persuasive elements, the implicit ones are the most frequent in the speech of the interlocutors. However, the host resorts to a discourse apparently friendly and capable of facilitating the exposure of the interviewee s opinion. The interviewee in most of her turns use monoglossic utterances